2010
DOI: 10.1093/schbul/sbq037
|View full text |Cite
|
Sign up to set email alerts
|

Neural Changes Associated With Relational Learning in Schizophrenia

Abstract: Relational learning, which is learning the relationship among items, is impaired in schizophrenia but can be improved with training. This study investigated neural changes with functional magnetic resonance imaging before and after training on a relational learning task in schizophrenia and healthy control subjects. Despite their acquiring similar relational learning performance, the groups exhibited different neural activation patterns before and following training. Controls engaged regions within the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…This adds the AIP to the already existing experimental paradigms that have demonstrated relational memory deficits in schizophrenia. 15,16,[39][40][41][42] The schizophrenia group was not uniformly impaired on the associative inference task. Ten patients with schizophrenia completed all components of the task, including the relational F1-F2 condition.…”
Section: Discussionmentioning
confidence: 87%
“…This adds the AIP to the already existing experimental paradigms that have demonstrated relational memory deficits in schizophrenia. 15,16,[39][40][41][42] The schizophrenia group was not uniformly impaired on the associative inference task. Ten patients with schizophrenia completed all components of the task, including the relational F1-F2 condition.…”
Section: Discussionmentioning
confidence: 87%
“…Stimuli for the TP and elemental verbal versions consisted of three pronounceable non-words for each task (see Figure 1, b and d). There has been evidence of less reliance on hippocampus as stimuli and their relations become more meaningful (Doeller et al, 2005; Moses et al, 2008, 2009), with patients diagnosed with schizophrenia not showing a behavioral deficit on the TP relational task that uses meaningful stimuli (Hanlon et al, 2005; Rowland et al, 2010). Although this idea has not been completely supported, with some believing the perirhinal cortex involved in familiarity (Diana et al, 2007), as a precaution stimuli and their relations were chosen to be as meaningless as possible in the present study.…”
Section: (2) Materials and Methodsmentioning
confidence: 99%
“…Logical Memory performance and IS trial response times). We interpret this to indicate that similar to schizophrenia patients (Rowland et al, 2010), individuals at-risk for schizophrenia likely utilize alternative strategies and/or different brain circuits to achieve relational memory. Rowland et al showed that compared to HC, schizophrenia patients have different patterns of fMRI activations following relational learning.…”
Section: Discussionmentioning
confidence: 95%
“…Episodic memory deficits in schizophrenia patients may be principally due to impairment in relational memory encoding (Ragland et al, 2012); which in turn have been associated with reduced dorsolateral prefrontal and hippocampal activations (Ragland et al., 2015). With regards to TI (a form of relational memory), schizophrenia patients performed poorly compared to healthy volunteers, and lower mean accuracy and longer mean response time (Armstrong et al, 2012a; Armstrong et al., 2012b; Coleman et al, 2010; Ongur et al, 2006; Rowland, Griego, Spieker, Cortes, & Holcomb, 2010; Titone et al, 2004). Furthermore, patients have greater difficulties in attaining adequate learning of the relational memory task (Armstrong et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%